Judicial reform: A process of change through pilot courts - (:unkn) unknown (My University, 2016)
One way to begin the judicial reform process is via a pilot program of court modernization.Courts usually have limited experience of reform processes. Pilotcourts can help the judiciary develop the tools needed to manage projectsand implement reforms, and can serve as the basis for much larger efforts.They foster teamwork, and can help identify and create leaders and trainpersonnel to carry the judiciary into future projects.